A Novel Cold-Adaptive Endo-1,4-β-Glucanase From Burkholderia pyrrocinia JK-SH007: Gene Expression and Characterization of the Enzyme and Mode of Action - Chen, Feifei; Ye, Jianren; Sista Kameshwar, Ayyappa Kumar; Wu, Xuelian; Ren, Jiahong; Qin, Wensheng; Li, De-Wei (Frontiers in Microbiology, 2020)
The efficient industrial conversion of plant-derived cellulose to simple sugars and other value-added chemicals requires various highly stable and reactive enzymes. Industrial processes especially synchronous saccharification and fermentation (SSF)-based production of cellulosic bio-ethanol require enzymes that are active at lower temperatures. In this study, we have identified, characterized and expressed the cold-adaptive endo-1,4-β-glucanase (BpEG) isolated from the Burkholderia pyrrocinia JK-SH007. The analysis of the predicted amino acid sequence indicated that BpEG belongs to GH family 8. The BpEG without the signal peptide was cloned into the expression vector pET32a and significantly expressed in Escherichia coli BL21(DE3) competent cells. The SDS-PAGE and Western blot analysis of BpEG revealed that the recombinant BpEG was approximately 60 kDa. Purified recombinant BpEG exhibited hydrolytic activity against carboxymethyl cellulose (CMC) and phosphoric acid swollen cellulose (PASC), but not crystalline cellulose and xylan substrates. High performance, anion exchange, chromatography-pulsed amperometric detector (HPAEC-PAD) analysis of the enzymatic products obtained from depolymerization of 1,4-β-linked biopolymers of different lengths revealed an interesting cutting mechanism employed by endoglucanases. The recombinant BpEG exhibited 6.0 of optimum pH and 35ºC of optimum temperature, when cultured with carboxymethyl cellulose (CMC) substrate. The BpEG enzyme exhibited stable activity between pH 5.0-9.0 at 35ºC. Interestingly, BpEG retained about 42% of its enzymatic activity at 10ºC compared to its optimal temperature. This new cold-adaptive cellulase could potentially achieve synchronous saccharification and fermentation (SSF) making BpEG a promising candidate in the fields of biofuel, biorefining, food and pharmaceutical industries.